Comparison of Physical Properties between Grey and Dyed Knitted Fabric - Jahan Khanam, Nusrath; Saha Swati, Sushama; Maliha, Mayesha; Mamun Pritha, Nadvi (European Scientific Journal, ESJ, 2022)
This paper focuses on the changes in the fabric’s physical properties like GSM, bursting strength, pilling, extension, and residual extension in both grey and dyed stage. Moreover, this investigation also shows the relationship between bursting strength, pilling, extension, and residual extension with GSM. Furthermore, from grey to dyed stage, a visible change in GSM occurred and the influence of GSM in different physical properties also appeared significantly. A strong relationship of bursting strength, extension, and residual extension with GSM change of 100% cotton single jersey fabric was found, but pilling shows very negligible change in relation to GSM. Physically, after dyeing, changes were visible in case of GSM and pilling. With the change of fabric condition, i.e., grey and dyed stage fabric, the physical properties shows significant changes in terms of characteristics. In comparison to different physical properties of fabric in grey and dyed stage, the analysis has shown that the value of GSM was increased gradually after dyeing. Bursting strength, extension, and residual extension was decreased from grey to dyed stage. Overall pilling rate was observed and it was found to improve after dyeing.